Perbandingan Kapasitas Sambungan Balok Kolom Sistem Konvensional Dengan Sistem Pracetak Yang Menggunakan Dywidag Ductile Connector (DDC) - Rachmat Hidayat; Zulfikar Djauhari; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Beam - column Joint is a critical part on a reinforced concrete frame structure which is designed specifically for inelastic deformating when obtain a strong earthquake . Beam - column Joint will get horizontal and vertical shear forces as a moment result from the column above and below it and moments of the beams when carry the load of the earthquake. Beam-column joint is a very important part when transfer forces between precast elements which are connected. Beam - column joint area should be planned well in order to avoid changes the force flow precast structure which result the collapse of the hierarchy which are achieved in the structure . when the system of structure is changed from conventional to precast, it should be needed a good analyze to get an accuracy capacity in the critical region structural elements . In this study is obtained a moment and shear capacity of the structure which is put on any type of soil between conventional beam-column connection and a precast use Dywidag Ductile Connector. The result show that there are a differences between two types of connections in moment and shear capacity what are placed in difference soil conditions . The greatest of moments capacity is in the conventional beam column connection, that is SE = 271.25kNm, SD = 222.40 kNm , SC = 199.35 kNm, SB = 162.20 kNm, SA = 162.20 KNm. While The greatest of shear capacity is in the precast beam column connection, that is SE = 1318.21 kN , SD = 1019.80 kN , SC = 1019.80 kN, SB = 878.80 kN, SA = 679.87 kN. it is caused of type of method in calculating for the capacity of conventional systems and precast connector with ductile connector type.Keyword : Precast, Conventional, Ductile Connector, Beam – Column Connection